Click-chemistry approach to study mycoloylated proteins: Evidence for PorB and PorC porins mycoloylation in Corynebacterium glutamicum. - Hanane Issa (PLoS ONE, 2017)
Protein mycoloylation is a recently identified, new form of protein acylation. This post-translational modification consists in the covalent attachment of mycolic acids residues to serine. Mycolic acids are long chain, α-branched, β-hydroxylated fatty acids that are exclusively found in the cell envelope of Corynebacteriales, a bacterial order that includes important genera such as Mycobacterium, Nocardia or Corynebacterium. So far, only 3 mycoloylated proteins have been identified: PorA, PorH and ProtX from C. glutamicum. Whereas the identity and function of ProtX is unknown, PorH and PorA associate to form a membrane channel, the activity of which is dependent upon PorA mycoloylation. However, the exact role of mycoloylation and the generality of this phenomenon are still unknown. In particular, the identity of other mycoloylated proteins, if any, needs to be determined together with establishing whether such modification occurs in Corynebacteriales genera other than Corynebacterium. Here, we tested whether a metabolic labeling and click-chemistry approach could be used to detect mycoloylated proteins. Using a fatty acid alkyne analogue, we could indeed label PorA, PorH and ProtX and determine ProtX mycoloylation site. Importantly, we also show that two other porins from C. glutamicum, PorB and PorC are mycoloylated.